High-Level Patchoulol Biosynthesis in Artemisia annua L. - Fu, Xueqing; Zhang, Fangyuan; Ma, Yanan; Hassani, Danial; Peng, Bowen; Pan, Qifang; Zhang, Yuhua; Deng, Zhongxiang; Liu, Wenbo; Zhang, Jixiu; Han, Lei; Chen, Dongfang; et al. (Frontiers in Bioengineering and Biotechnology, 2021)
Terpenes constitute the largest class of secondary metabolites in plants. Some terpenes are essential for plant growth and development, membrane components and photosynthesis. Terpenes are also economically useful for industry, agriculture and pharmaceuticals. However, there is very low content of most terpenes in microbes and plants. Chemical or microbial synthesis of terpenes are often costly. Plants have the elaborate and economic biosynthetic way of producing high-value terpenes through photosynthesis. Here we engineered the heterogenous sesquiterpenoid patchoulol production in A. annua. When using a strong promoter such as 35S to over express the avian farnesyl diphosphate synthase gene and patchoulol synthase gene, the highest content of patchoulol was 52.58 μg/g DW in transgenic plants. When altering the subcellular location of the introduced sesquiterpene synthetase via a signal peptide, the accumulation of patchoulol was observably increased to 273 μg/g DW. This case demonstrated that A. annua plants with glandular trichomes is a useful platform for synthetic biology studies.